Bioplastic from Cassava peel and eggshell waste - Nila Tanyela Berghuis; Diah Kemala Mutmainah; Meliana Nur Savitri; Meri Arizki; Dyas Dwi Yunita; Fahdly Awaluddin; Rehan Rizkyta Peranginangin; Athirah Nursalsabila; Ris Kevin Bramasta (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
The accumulation of plastic waste and excessive use of plastic is a common environmental issue in Indonesia. Plastics are synthetic polymers that are stable, water-resistant, light, flexible, and firm but very difficult to break down by microorganisms. Decomposition of plastic waste by burning can cause other environmental issues and, during the combustion process can produce dioxin compounds that are harmful to health. An available and affordable alternative to reduce the use of plastic is by using bioplastics. Bioplastics are plastics made from natural materials that microorganisms can break down, so they are more environmentally friendly than commercial plastics. Generally, the main ingredients for making bioplastics are starch or chitosan. The source of starch used in this project comes from cassava peel waste. In this project, researchers also utilize waste from chicken eggshells. The function of adding eggshell waste is to give biodegradable plastic complex characteristics. The ratio between cassava peel and eggshell used was 1:0, 1:1, 1:3, and 1:5. With a 1:1 ratio is the most optimal. The addition of eggshells with the correct ratio (1:1) increased the ability of biodegradation of bioplastics. The results of the Tensile Strength Test of Bioplastic Samples with a ratio of 1:0, 1:1, 1:3, and 1:5 are 9.2 x10-3kgf/cm2, 4.4 x10-3 kgf/cm2, 2 x10-3 kgf/cm2, and 2 x10-3 kgf/cm2.©2022 JNSMR UIN Walisongo. All rights reserved.